DETECTION OF PROTEIN CD2AP IN MICE(Mus musculus) KIDNEY DAMAGE INDUCED BY NaCl 4% - Septya, Lia
Chronic kidney disease (CKD) is a serious problem with an increasing prevalence and incidence of kidney failure. Patient with hypertension have progress towards manifestasions of nephrophaty syndrome characterized by proteinuria. Detection of increased of protein excretion is known to confirm kidney disease. CD2-associated protein (CD2AP) is a protein molecule expressed in the kidneys in parts of podocytes. The appearance of this protein molecule in urine is consistent with changes in renal function index in blood and urine samples of patients with acute renal failure. Whereas in clinical histopathology, kidney damage with indications of proteinuria is characterized by Focal Segmental Glomerulosclerosis (FSGS). The purpose of this study was to detect CD2AP protein as an early indicator of kidney damage and determine CD2AP protein concentration against the stages of kidney damage through three main parameters, namely quantification of urine CD2AP protein and serum creatinine confirmed by glomerular histopathology. The study involved 24 male models of mice (Mus musculus) from Swiss webster lines divided into 6 research groups, namely three Control Groups (KK) and three Treatment Groups (KP) Hypertension with 4% NaCl induction every day for 2, 4 and 6 weeks. Quantitative analysis was carried out to determine the concentration of CD2AP protein using Sandwich ELISA technique in urine samples and creatinine levels in serum using the Jaffe method followed by qualitative analysis in the form of FSGS as histopathological kidney which display from each group. The results showed that there were significant differences between each treatment group of hypertension and the control group (P?0,05), whereas each hypertension treatment group showed differences but not significant (P?0,05) The serum creatinine test did not show a significant difference (P?0,05) between the control groups when compared with the creatinine concentration of the treatment group. Kidney histopathology displays FSGS formation progress at week 4 to global indications of sclerosis in the 6th week treatment group. From the results of this study it can be concluded that the presence of CD2AP protein in urine can be used as an early indicator of kidney damage but cannot show a significant difference in the stage of kidney damage.